S27. EXAMINING DISCREPANCIES BETWEEN SELF-REPORT AND CLINICIAN-RATED ASSESSMENTS OF PSYCHOSIS RISK: DOES INTERNALIZED STIGMA MATTER?. (18th May 2020) - Shan, LeeAnn; Millman, Zachary B; DeLuca, Joseph; Klaunig, Mallory J; Rouhakhtar, Pamela Rakhshan; Lucksted, Alicia; Medoff, Deborah R
Abstract: Background: Psychosis is one of the most highly stigmatized mental health conditions (Thornicroft et al., 2009). Compared to those with other mental health concerns, people diagnosed with schizophrenia spectrum disorders are more likely to be perceived by others as dangerous, violent, and unpredictable. As a result, they are often socially marginalized and discriminated against (Crisp et al., 2000; Martin et al., 2007). Individuals at clinical high risk (CHR) for psychosis may be at lower risk for experiencing public stigma, given that their symptoms are often less outwardly visible at this early stage of illness. However, evidence suggests that those at CHR experience high levels of self-stigma, as they may internalize negative stereotypes related to psychosis (Yang et al., 2010; Yang et al., 2015). Internalized stigma can negatively impact help-seeking behavior and has been associated with lower self-esteem and the underreporting of mental health symptoms (Corrigan, 2004; Corrigan, 2007; Saporito, Ryan, & Teachman, 2011; Rüsch, Angermeyer, & Corrigan, 2005). Despite these findings, no studies to-date have examined how internalized stigma may impact reporting of attenuated psychosis symptoms in the CHR population. The current study aims to examine whether discrepancies between self-report and clinician-rated measures of psychosis risk are associated with internalized stigma in a sample of help-seeking adolescents and young adults. We hypothesized that higher levels of self-stigma will predict inconsistencies between self-reported symptom severity and clinician-obtained diagnoses of psychosis risk. Methods: Participants will include youth classified as either non-psychosis-related help-seeking controls or at clinical high risk (CHR) for psychosis, as determined by the Structured Interview for Psychosis-Risk Syndromes (SIPS; Miller et al., 2003). The SIPS is administered by trained raters and is currently considered the gold standard tool for diagnosing clinical high-risk syndromes (Thompson et al., 2018). In addition to SIPS diagnoses, psychosis risk will also be assessed using the Prime Screen – Revised (PS-R; Miller et al., 2004), a brief, 12-item self-report questionnaire designed to measure attenuated positive symptoms. Lastly, internalized stigma will be assessed using the Internalized Stigma of Mental Illness Inventory (ISMI; Ritsher, Otilingam, & Grajales, 2003), a 29-item self-report questionnaire designed to measure subjective experiences of stigma in adolescents (e.g., endorsement of negative stereotypes, social withdrawal and feelings of alienation due to mental health problems, etc.). Results: Preliminary analyses demonstrate a significant interaction between Prime scores and internalized stigma in predicting SIPS diagnoses. Specifically, higher scores on the Prime were associated with increased odds of being diagnosed as CHR on the SIPS, but only for those participants who endorsed low and mean levels of stigma. For participants who endorsed high levels of stigma, there did not appear to be any relation between Prime scores and SIPS diagnoses. Discussion: At the time of submission, participant recruitment is ongoing, and results and discussion will be presented on the final sample. Findings may inform efforts to improve detection and accurate diagnosis of psychosis risk syndromes in individuals at early stages of illness.